Propensity to learning difficulties and developmental problems in university students from the Peruvian Amazon. - Paricahua Peralta, Jimmy N.; Estrada Araoz, Edwin G.; Zevallos Pollito, Percy A.; Velasquez Giersch, Libertad; Mora Estrada, Osbel; Rivera Mamani, Gladys Filonila; Ulloa Gallardo, Nelly Jacqueline; Roque Guizada, Cesar E. (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
The study aimed to describe the propensity of Peruvian university students to learning difficulties, developmental problems and other difficulties related to university work. A descriptive investigation was carried out with two samples made up of 119 students belonging to the 2020-I semester and 169 from the 2020-II semester. The DASS-21 scale was used for anxiety, depression and stress; the Pittsburgh Sleep Quality Questionnaire, the Brief CBA Questionnaire, and the Questionnaire to Identify Learning, Sensory, and Motor Difficulties. The results indicate that students were more prone to difficulties related to sleep deprivation, difficulties with mathematics, non-pathological anxiety, difficulties with writing, spelling and reading comprehension and, lastly, visual limitations. Finally, it was concluded that there are learning difficulties, sleep deprivation, adjustment disorder with depressed mood states and permissible alcohol use disorder in university students in the Peruvian Amazon.